2020
DOI: 10.1016/j.pcd.2019.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic control in Kuwaiti diabetes patients treated with glucose-lowering medication

Abstract: Background: Diabetes is prevalent in Kuwait. We aimed to assess the level of glycemic control in Kuwaiti adults with diabetes. Method:The World Health Organization's STEPS non-communicable disease risk factor survey was conducted in Kuwait in 2014. Participants' demographics, medical history, physical measurements and blood biochemistry were assessed. A total of 2,561 Kuwaiti men and women aged 18-69 years completed all three survey steps. Glycemic control in 278 individuals with diabetes who were on glucose-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 53 publications
4
12
0
Order By: Relevance
“…Other studies in Jordan, Kuwait, Bosnia, Nepal, Lebanon, Malaysia and Italy reported 23 to 43% of the prevalence of very good glycemic control, which was roughly the same as our study. Most studies assumed the diversity of glycemic control status to be due to the difference in sample size, duration of DM, and the degree of medication adherence [3,4,9,[16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies in Jordan, Kuwait, Bosnia, Nepal, Lebanon, Malaysia and Italy reported 23 to 43% of the prevalence of very good glycemic control, which was roughly the same as our study. Most studies assumed the diversity of glycemic control status to be due to the difference in sample size, duration of DM, and the degree of medication adherence [3,4,9,[16][17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that DM will involve about 9.2 million of Iranians by the year 2030. Prevalence of DM, especially type 2 DM (T2DM), is nowadays aggressively increasing due to sedentary lifestyles and consumption of unhealthy foods [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…The results of glycemic control observed in patients with DM2 is low, so an approach is considered where a strategy is sought to improve knowledge about their disease and their adherence to treatment [4]. DM2 is one of the diseases that is most associated with cardiovascular diseases; studies have shown that glycemic control reduces diabetic vascular complications [3].…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes is an incessant chronic condition where it causes a high level of sugar in the blood [3]. This is due to the decrease in the mechanism of beta cells of the pancreas [4], generating various stimuli in various parts of the body, among them, they are pancreatic failure, increased risk of cardiovascular system diseases, hypertension, kidney failure, neuropathy, problems with foot vascularization, ketoacidosis, visual problems, among others [5], [6].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, PA achieves several healthcare goals such as [18,19], reducing the risk of cardiovascular disease (CVD) [20,21], increasing the vigour [22], reducing levels of triglyceride-rich VLDL [23], decreasing the insulin resistance [24,25], improving the blood pressure (BP) [26,27], preventing the obesity [28,29], reducing the mortality [30,31] [32,33], enhance cognitive performance [34], enhance the mood [35], and increasing the energy expenditure [36,37]. In recent years, several glucose-monitoring techniques have been conducted [38][39][40][41][42]. Based on the literature, still there is a lack of clarity about what level of physical activity is needed to reduce the risk of T2D [43,44].…”
Section: Introductionmentioning
confidence: 99%